Los pollitos hacen de las suyas = Chicks run wild - Bardhan-Quallen, Sudipta; Jenkins, Ward (New York : Simon & Schuster Books for Young Readers, 2011)
When her little chicks refuse to settle down for the night, Mama decides to surprise them with an unusual request.
"Compliments of Cheerios"--Cover verso
AD 530
Accelerated Reader
Keywords: Stories in rhyme -- Juvenile literature; Chickens -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Bedtime -- Juvenile fiction; Mother and child -- Juvenile fiction